ANALISA ESKALASI BIAYA PADA PROYEK INFRASTRUKTUR TAHUN JAMAK (Studi Kasus : Proyek Pembangunan Waduk Jatigede dan Proyek Pembangunan Waduk Jatibarang) - Alif Fatoni; Muhammad Hanif; M. Agung Wibowo; Jati Utomo Dwi Hatmoko (Jurnal Karya Teknik Sipil, 2013)
One of risk of multi years project contract is price adjustment. So, the government issued rules regarding price adjustments through Presidential Decree No. 70/2012 Article 92 that completes the previous rules. Rules about the price adjustment are described in more detail in the contract documents. This situation has led to the price adjustment calculations between different projects. The purpose of this study is to analyze the value of an escalation in the ongoing work items in Jatigede DamProject and Jatibarang Dam Project. Hopefully, through this research, regulation application number 70/2012 on contract documents related to price adjustment.The research was conducted by interview, field observation and simulation calculations based of Jatigede Dam Project and Jatibarang Dam Project contract documents  in data processing. Jatibarang Dam Project assign the value of contract component based on HPS (Owner Cost Estimate) from survey and set the index of economic indicators published by BPS. Jatigede Dam Projectassigns a value based on the cost factor analysis and establishes the unit price indices through the Wholesale Price Index and Consumer Price Index in Cirebon City. This research simulates the price adjustment by exchanging contract documents on both projects with the volume of work in March 2011 and April 2011. Simulation methods on Jatibarang Project generate escalations value 15.69% and 15.44% from the value of escalation methods Jatigede Dam Project. Simulation methods Jatigede Dam Project escalation generate value 175.03% and 161.35% of the value of escalation with methods Jatibarang Dam Project.